Yellow Book Learning Transformation Bandongan Tradition at Qomaruddin Islamic Boarding School Gresik - Mochamad Chairudin (Dirosatuna: Journal of Islamic Studies, 2023)
A tradition is an act that is repeated in the same way. Pondok Pesantren Qomaruddin Gresik uses the Bandongan Tradition to learn to understand the yellow book. This study wants to know the process of transforming the study of the yellow book through the Bandongan tradition at the Qomaruddin Gresik Islamic boarding school. The research uses ethnomethodological and phenomenological logical thinking. The process of searching for this data follows the snowball sampling principle. Sources of data used are library data (documents or archives), field data (resources or informants), and events or activities with data collection procedures using observation, interviews, and documentation. Using qualitative data analysis, the data obtained is analyzed using non-statistical descriptive methods by means of inductive thinking. The Qomaruddin Islamic Boarding School succeeded in reforming the habit because it did not break the chain of continuity between the past and the present (adopting new, better methods).